The Routledge Handbook of Housing Policy and Planning - Anacker, Katrin B.; Nguyen, Mai Thi; Varady, David P. (Routledge, 2020)
The Routledge Handbook of Housing Policy and Planning provides a comprehensive multidisciplinary overview of contemporary trends in housing studies, housing policies, planning for housing, and housing innovations in the United States, the United Kingdom, and Continental Europe. In 29 chapters, international scholars discuss aspects pertaining to the right to housing, inequality, homeownership, rental housing, social housing, senior housing, gentrification, cities and suburbs, and the future of housing policies. This book is essential reading for students, policy analysts, policymakers, practitioners, and activists, as well as others interested in housing policy and planning.